Regulation of Foreign Workers Based on Job Creation Act of Maslahah Perspective - Siti Nur Fitriana; Iffatin Nur (JURIS (Jurnal Ilmiah Syariah), 2021)
The Omnibus Law Bill which has been passed into law number 11 of 2020 concerning Work Creation has generated a lot of controversy in the community. One of the articles that is most highlighted is related to foreign workers, in which the licensing is made easier. For this reason, this regulation needs to be studied from the perspective of maslahah. The purpose of this study is to determine the regulation of foreign workers after the work copyright law and its maslahah perspective. The research method used is normative juridical research with a statute approach and a conceptual approach. The results of this study indicate that Article 42 of the Job Creation Law contains a permit for the use of foreign workers using only RPTKA. In addition, the positions of foreign workers that do not require RPTKA are expanded and added to the positions of directors, commissioners and foreign workers needed in an emergency situation. Furthermore, details of the RPTKA were also deleted. In terms of maslahat, the regulation of foreign workers based on the Job Creation Law is not yet in accordance with the concept of maslahat, because the benefit is only for some people, not for the general benefit.